Clinical and Laboratory Profile and Therapeutic Response of Scrub Typhus in Children in a Tertiary Care Centre in Nepal - Agrawal, Sumit; Subedi, Krishna Hari; Shah, Rajesh Kumar; Jha, Santoshanand; Pun, Sher Bahadur (Birat Journal of Health Sciences, 2020)
Introduction Scrub typhus is the most common ricketisial infection from the Indian subcontinent. It is caused by the organism Orienta tsutsugamushi inhabiting in trombiculid mites and transmitied to humans by the bite of these mites. The disease has a variety of clinical manifestations in children. As this is a common disease in our country so a retrospective study was conducted to study the clinical and laboratory profile and therapeutic outcomes of scrub typhus in children.Methodology A retrospective study was conducted at Sukraraj Tropical and Infectious disease Hospital, Teku, Kathmandu, Nepal after obtaining ethical clearance from Institutional Review Committee, and reviewing the medical records of serologically confirmed scrub typhus in children aged less than 14 years admitted to the hospital between March 2017 and February 2018. Relevant data were entered in excel spreadsheet and analyzed using SPSS 20.Result A total of 20 children were enrolled in the study. Of them 70% were female, with the mean age being 11.45 ± 3.1 years (range 3-14 years) and majority were from Dhading district (40%). All the children had fever; while there was cough, loss of appetite, rashes, headache, myalgia, arthralgia and hepatosplenomegaly in 45%, 90%, 20%, 55%, 35%, 35% and 30% of children respectively. There was thrombocytopenia in 50% of children; while hyponatremia, elevation of SGOT and SGPT was present in 30%, 70% and 55% of patients respectively. Azithromycin was used for treatment in 95% of children and all had defervescence of fever.Conclusion Scrub typhus should be suspected in children having prolonged fever with organomegaly, thrombocytopenia and elevated transaminases. Azithromycin can be used effectively in children diagnosed as scrub typhus.